Unusual length dependence of the conductance in cumulene molecular wires - Xu, W; Leary, E; Hou, S; Sangtarash, S; González, M; Rubio-Bollinger, G; Wu, Q; Sadeghi, H; Tejerina, L; Christensen, K; Agraït, N; Higgins, S; et al. (Wiley, 2019)
Cumulenes are sometimes described as “metallic” because an infinitely long cumulene would have the band structure of a metal. Herein, we report the single‐molecule conductance of a series of cumulenes and cumulene analogues, where the number of consecutive C=C bonds in the core is n=1, 2, 3, and 5. The [n]cumulenes with n=3 and 5 have almost the same conductance, and they are both more conductive than the alkene (n=1). This is remarkable because molecular conductance normally falls exponentially with length. The conductance of the allene (n=2) is much lower, because of its twisted geometry. Computational simulations predict a similar trend to the experimental results and indicate that the low conductance of the allene is a general feature of [n]cumulenes where n is even. The lack of length dependence in the conductance of [3] and [5]cumulenes is attributed to the strong decrease in the HOMO–LUMO gap with increasing length.